Detrimental impact of immunosuppressive burden on clinical course in patients with Cytomegalovirus infection after liver transplantation - Ossami Saidy, Ramin Raul; Kollar, Stefanie; Czigány, Zoltán; Dittrich, Luca; Raschzok, Nathanael Johannes; Globke, Brigitta; Schöning, Wenzel; Öllinger, Robert; Lurje, Georg; Pratschke, Johann; Eurich, Dennis; Uluk, Deniz (Transplant infectious disease, 2023)
Introduction Cytomegalovirus (CMV)-infection and reactivation remain a relevant complication after liver transplantation (LT). The recipient and donor serum CMV-IgG-status has been established for risk stratification when choosing various pharmaceutical regimens for CMV-prophylaxis in the last two decades. However, factors influencing course of CMV-infection in LT remain largely unknown. In this study, the impact of immunosuppressive regimen was examined in a large cohort of patients. Methods All patients that underwent primary LT between 2006 and 2018 at the Charité-Universitaetsmedizin, Berlin, were included. Clinical course as well as histological and laboratory findings of patients were analyzed our prospectively maintained database. Univariate and multivariate regression analysis for impact of variables on CMV-occurrence was conducted, and survival was examined using Kaplan-Meier analysis. Results Overall, 867 patients were included in the final analysis. CMV-infection was diagnosed in 325 (37.5%) patients after transplantation. Significantly improved overall survival was observed in these patients (Log rank = 0.03). As shown by correlation and regression tree classification and regression tree analysis, the recipient/donor CMV-IgG-status with either positivity had the largest influence on CMV-occurrence. Analysis of immunosuppressive burden did not reveal statistical impact on CMV-infection, but statistically significant inverse correlation of cumulative tacrolimus trough levels and survival was found (Log rank < .001). Multivariate analysis confirmed these findings (p = .02). Discussion CMV-infection remains of clinical importance after LT. Undergone CMV-infection of either recipient or donor requires prophylactic treatment. Additionally, we found a highly significant, dosage-dependent impact of immunosuppression (IS) on long-term outcomes for these patients, underlying the importance of minimization of IS in liver transplant recipients.